Pelaksanaan Pembelajaran Secara Daring Mata Pelajaran Bahasa Indonesia di SMAN 1 Nan Sabaris - Mulyani, Sri; Atmazaki, Atmazaki (Journal of Education Language and Innovation, 2023)
This study aims to describe the way teachers in presenting and interacting in the online learning process of Indonesian subjects and to describe the study of Indonesian online learning subjects at State High School 1 Nan Sabaris. This is qualitative research with descriptive methods. The qualitative data were collected by using observation, interviews, and documentation techniques. The quantitative data were collected by using a questionnaire. The data sources in this study are two teachers of Indonesian subjects, the principal, and 30 students at SMA Negeri 1 Nan Sabaris. The instruments in this study are the researchers themselves for qualitative data and for quantitative data instruments are questionnaires. Data is analyzed by describing, analyzing, and discussing data based on theory. The theory used is related to the theory of online learning in Indonesian subjects. The results showed that the implementation of online learning subjects Indonesian at Sma Negeri 1 Nan Sabaris has been implemented but not yet maximal. The obstacles faced by teachers Indonesian are most widely found are unstable internet networks, technological limitations, and the neglect of students in the collection of tasks. The efforts of teachers to overcome the obstacles obtained in the implementation of online learning have not been fully resolved. Signal and technology constraints, for now, can not be overcome by teachers, but related to dereliction of duty, teachers always monitor and remind students to keep carrying out their duties well in the implementation of online learning in Indonesian learning.